Functional brain effects of acute concussion in Australian rules football players. (July 2019) - Jackson, Graeme D; Makdissi, Michael; Pedersen, Mangor; Parker, Donna M; Curwood, Evan K; Farquharson, Shawna; Connelly, Alan; Abbott, David F; McCrory, Paul
Aim: To determine whether acute sport-related concussion is associated with functional brain changes in Australian rules footballers. Methods: Twenty acutely concussed professional Australian footballers were studied with 3 T magnetic resonance imaging and compared to 20 age-matched control subjects. We statistically compared whole-brain local functional magnetic resonance imaging connectivity between acutely concussed footballers and controls using voxel-wise permutation testing. Results: The acutely concussed football players had significantly decreased local functional magnetic resonance imaging connectivity in the right dorsolateral prefrontal cortex, right inferior parietal lobe, and right anterior insula, compared to controls. No functional brain changes between groups within the default mode network were observed. Discussion: Acutely concussed footballers had in common decreased functional connectivity within the right lateralized "cognitive control network" of the brain that is involved in executive functions, and the "salience network" involved in switching between tasks. Dysfunction of these brain regions is a plausible explanation for typical clinical features of concussion.